1999
DOI: 10.1002/(sici)1097-0207(19991130)46:9<1421::aid-nme706>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

A mixed elastoplastic/rigid–plastic material model

Abstract: A new integration algorithm is described for large strain plastic deformations. The algorithm degenerates to the Euler forward elastoplastic-plastic model for small strain increments and to the rigid-plastic model for large strain increments. The model benefits from the advantages of both models: accuracy and fast convergence over a large range of strain increments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Taking = 1 2 coincides with the trapezoidal rule (mean normal), = 1 results in Euler backward integration (radial return). Huà etink et al [12] suggested to take as a function of the plastic multiplier in order to obtain an algorithm that is a mix between an elastoplastic and a rigid plastic method. This suggestion is elaborated in this paper to deÿne a class of adaptive integration algorithms for elasto-viscoplastic materials.…”
Section: Time Discretizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking = 1 2 coincides with the trapezoidal rule (mean normal), = 1 results in Euler backward integration (radial return). Huà etink et al [12] suggested to take as a function of the plastic multiplier in order to obtain an algorithm that is a mix between an elastoplastic and a rigid plastic method. This suggestion is elaborated in this paper to deÿne a class of adaptive integration algorithms for elasto-viscoplastic materials.…”
Section: Time Discretizationmentioning
confidence: 99%
“…In other words, the integral is approximated by a weighted combination of the plastic-strain direction at the start and the end of the increment. Huà etink et al [12] proposed a model in which the constant weights of the generalized trapezoidal rule are replaced by weights dependent on the plastic multiplier. In this way an elastoplastic model was derived that degenerates to the rigid plastic model for large strain increments.…”
Section: Introductionmentioning
confidence: 99%